SÍNTESE DE MATERIAL PARTICULADO AMARELO A BASE DE TiO2 CONTENDO MoO3 E Bi2O3 - Silva, Renata Martins da (2013)
Was synthesized particulate material based on containing a small amount of bismuth compounds and molybdenum with satisfactory reproducibility. The material was produced starting from a composition of 99% (mol %) of rutile TiO2 and 1% of MoO3, which were previously mixed and calcined at 1200ºC. The composition studied consisted of 99.8% of the above mixture and 0.2% of bismuth subnitrate hexahydrate, Bi5O(OH)9 NO3)4.6H2O. This powder mixture [(99.8% of TiO2+MoO3 and 0.2% of Bi5O(OH)9 (NO3)4.6H2O)] was homogenized and calcined in tubular furnace at 1200ºC using four different heating rates: 1, 30, 40 e 60 °C/min. The ascalcined powder was characterized by X-ray diffraction (XRD) for identification of the phases resulting, scanning electron microscopy (SEM) to evaluate the microstructure and degree of gglomeration of powders and particle size was estimated by laser scattering technique. The color properties were expressed as CIEL*a*b* coordinates. X-ray patterns indicated the presence of TiO2, Bi2O3, γ-Bi2MoO6, Bi2Ti2O7, Bi2Ti4O11 depending on the heating rate. The yellow color was attributed to the presence of α-Bi2O3, Bi2MoO6 e Bi2Ti2O7. The different heating rates showed no relevant influence on the powder morphology, but the particle size of the powder was suitable for using the material as an inorganic pigment.